Implementation of Piaget's Cognitive Development Theory in Learning at Modern Pesantren - Zaki Faddad Syarif Zain; Nyayu Soraya; Baldi Anggara (LPPPM STAI Darul Hikmah Bangkalan, 2026)
This study examines the application of Piaget’s cognitive development theory in learning practices at the Moderen Pesantren Prof. Muhajirin in Palembang. The research employed a descriptive qualitative approach using observations, interviews with teachers and pesantren administrators, and analysis of learning documents. The findings indicate that students aged 12–15 years are in the formal operational stage, characterized by the ability to think abstractly, logically, and systematically. Learning activities at the pesantren are designed to support these cognitive abilities through inquiry-based, discussion-based, problem-based, and scientific learning approaches. These approaches are implemented through educational activities such as muhadharah, group discussions, youth scientific work (KIR), and public examinations. The results show that Piaget’s cognitive development theory can support more reflective, analytical, and participatory religious learning within the pesantren environment. However, this study is limited to a single institutional setting and relies primarily on qualitative observations, which may limit the generalizability of the findings. Future studies are therefore needed to examine the application of cognitive development theory in diverse Islamic educational contexts using more comprehensive research designs